Successful School Leadership in the USA: The Role of Context in Core Leadership Practices - Lauri Johnson; Peter Moyi; Rose M. Ylimaki (MDPI AG, 2023)
This article draws on findings from a secondary analysis of selected U.S. case studies of successful school principals in the United States. All original ISSPP cases were selected with a common sampling strategy whereby we purposely selected schools with improved student outcomes and nominations by school district leaders and organizations. Data sources include semi-structured qualitative interviews with the district leaders, principal, teachers, parents, and students to provide a more elaborated understanding of the phenomena, i.e., school success and the principal's leadership contribution. The study selected twenty published articles describing complete ISSPP case studies from different U.S. geographic areas for secondary analysis of the principal's core leadership practices. These practices include setting directions, developing people, redesigning the organization, and managing the instructional program. The U.S. cases since 2002 reflect the dynamics of multiple layers of influence and increasing complexities from student diversity, policy pressures, and the impact of the principals' background and professional identity. These cases provide qualitative, contextualized understandings of school success and principal contributions to that success at particular points in time over the past 20 years and point toward knowledge gaps that we seek to fill in future steps of ISSPP.